Pengaruh Literasi Ekonomi Syariah terhadap Produktivitas Peternak Sapi dalam Meningkatkan Kesejahteraan Masyarakat - Ahmad Magafiratullah; Andi Patimbangi; Jumriani Jumriani (Studia Economica : Jurnal Ekonomi Islam, 2025)
This study aims to help understand how the influence of Islamic economic literacy can affect the productivity of cattle breeders in improving the welfare of the community, especially in the Cina District area, which has not been discussed enough in previous studies. Currently, livestock farming is a strategic sub-sector for achieving national food security and improving nutrition however, in reality, the livestock sector often faces various complex challenges, such as limited access to technology, limited capital, and unstable markets. This research is a descriptive study using quantitative methods. Purposive Sampling is the sampling technique used. The number of samples in this study took 100 respondents who were used as research samples based on the results of the calculation of the lemeshow formula used. Primary data was collected through a questionnaire distributed to respondents via Google Form. Structural Equation Modeling (SEM) is a component-based data analysis technique that utilizes the Partial Least Squares (PLS) analysis tool. The results of the hypothesis test (t-statistic) of the Sharia Economic Literacy variable show a t-statistic of 5.817 > 1.96 and a p-value of 0.000 < 0.05. Based on the results of this study, it is proven that Sharia Economic Literacy (X) has a significant influence on the Productivity of Cattle Breeders (Y) in improving the welfare of the community in Cina District